A New Approach to Modify Plant Microbiomes and Traits by Introducing Beneficial Bacteria at Flowering into Progeny Seeds - Mitter, Birgit; Pfaffenbichler, Nikolaus; Flavell, Richard; Compant, Stéphane; Antonielli, Livio; Petric, Alexandra; Berninger, Teresa; Naveed, Muhammad; Sheibani-Tezerji, Raheleh; von Maltzahn, Geoffrey; Sessitsch, Angela (Frontiers in Microbiology, 2017)
The microbial component of healthy seeds - the seed microbiome - appears to be inherited between plant generations and can dynamically influence germination, plant performance, and survival. As such, methods to optimize the seed microbiomes of major crops could have far-reaching implications for plant breeding and crop improvement to enhance agricultural food, feed and fiber production. Here, we describe a new approach to modulate seed microbiomes of elite crop seed embryos and concomitantly design the traits to be mediated by seed microbiomes. Specifically, we discovered that by introducing the endophyte Paraburkholderia phytofirmans PsJN to the flowers of parent plants we could drive its inclusion in progeny seed microbiomes, thereby inducing vertical inheritance to the offspring generation. We demonstrated the introduction of PsJN to seeds of monocot and dicot plant species and the consequential modifications to seed microbiome composition and growth traits in wheat, illustrating the potential role of novel seed-based microbiomes in determining plant traits.